"If a black hole is an oyster, then . . .": The discoursal trends of popularization in science fiction movies. (October 2021) - Babaii, Esmat; Asadnia, Fatemeh
Science fiction movies could play a pivotal role in making scientific discoveries available to the public. In this study, we explored the dialogue-based strategies these movies employ to appealingly communicate science. To investigate the discursive resources these movies use to represent science, we analyzed the content of 10 award-winning science fiction movies over the last decade (2010–2019). The findings demonstrated that although these movies deploy certain discursive features such as pseudoscientific hints, question markers, probability signals, statistical estimates, science boosters, paradox clues, comparison markers, exemplification, and figurative language that may influence audience thought patterns and a critical-reflective attitude toward science, they predominantly represent a partial distorted version of science characterized by inconsistency, inaccuracy, and skepticism. The study posits implications for science communicators to safeguard the legitimacy of science.